Mapping of Submarine Geomorphological Structures Using Satellite-Derived Bathymetry and Depth Data in the Waters of Lambasina Island, Kolaka Regency - Prasetya, Muhammad Iqra; Siregar, Vincentius Paulus; Agus, Syamsul Bahri (Jurnal Kelautan Tropis, 2025)
This research examines the geomorphological characteristics of the seabed around Lambasina Besar and Lambasina Kecil Islands, Kolaka Regency, by integrating Satellite-Derived Bathymetry (SDB) and the Benthic Terrain Modeler (BTM). Depth estimates were derived from Sentinel-2 imagery using the Support Vector Machine (SVM) algorithm and compared with in-situ depth measurements. The validation results indicated a high level of agreement, with R² values ranging from 0.81 to 0.82. The bathymetric data were then processed using Bathymetric Position Index (BPI), slope, and rugosity parameters, which allowed the classification of the seafloor into 13 geomorphological structure classes. The analysis identified various seabed forms, including flat plains, steep slopes, broad slopes, ridges, narrow depressions, and localized basins. These morphological patterns correspond well with coral reef zonation observed in the field. The findings highlight the important role of geomorphological variability in shaping benthic habitats and influencing biodiversity distribution. This approach demonstrates strong potential for supporting marine spatial analysis, conservation planning, and the identification of areas suitable for marine protection. Moreover, the study provides a basis for further research on the relationships between habitat complexity, biomass, coral diversity, and reef-associated fish abundance, which are essential for advancing ecosystem-based coastal management strategies.